PENGARUH PEMBELAJARAN SENI MENGGAMBAR TERHADAP PENINGKATAN KONSENTRASI PADA ANAK USIA DINI - Fasihah, Alya; Hidayah, Sri Wahyu; Faisal, Vava Imam Agus (JOURNAL FASCHO : JURNAL PENELITIAN DAN PENDIDIKAN ANAK USIA DINI, 2024)
Early Childhood Education (ECE) serves as a crucial foundation for children's development, honing their potential through various beneficial activities. Artistic activities, particularly drawing, play a vital role in cognitive development and concentration enhancement in young children. This article examines the relationship between drawing and the improvement of concentration in early childhood. Utilizing a qualitative approach based on library research, various psychological theories such as Multiple Intelligences Theory, Piaget's Cognitive Theory, and Csikszentmihalyi's Flow Theory are explored to understand the mechanisms behind this phenomenon. Findings indicate that drawing not only stimulates creativity but also enhances children's focus and attention through sensory-motor stimulation, emotional involvement, and structured creative processes. Educators and parents can utilize drawing as an effective tool to boost children's concentration abilities and cognitive development.